Imaging the pulmonary extracellular matrix. Issue 22 (August 2021) - Wijsman, Pieta C; van Smoorenburg, Lisa H; de Bruin, Daniël M; Annema, Jouke T; Kerstjens, Huib AM; Mets, Onno M; van den Berge, Maarten; Bonta, Peter I; Burgess, Janette K
Graphical abstract: Abstract : The pulmonary extracellular matrix (ECM) plays an important role in the structure and function of the lung. In many respiratory diseases the profile of the ECM reflects pathological changes. The capacity to visualize the ECM and its alterations is of considerable importance to facilitate a better understanding of pulmonary diseases and eventually augment therapeutic solutions. This short review summarizes the current and novel possibilities for imaging the pulmonary ECM by the use of computed tomography (CT), optical coherence tomography (OCT), confocal laser endomicroscopy (CLE) and molecular imaging. While not all these techniques are as yet implemented in standard clinical practice, we address their main features along with the key possibilities for the future.